Cu(II) Complexes of Isoniazid Schiff Bases: DNA/BSA Binding and Cytotoxicity Studies on A549 Cell Line. (21st July 2014) - Ramadevi, Pulipaka; Singh, Rinky; Prajapati, Akhilesh; Gupta, Sarita; Chakraborty, Debjani
Abstract : A series of isonicotinoyl hydrazones have been synthesized via template method and were complexed to Cu(II). The ligands are coordinated to Cu(II) ion through the enolic oxygen and azomethine nitrogen resulting in a square planar geometry. The CT-DNA and bovine serum albumin binding propensities of the compounds were determined spectrophotometrically, the results of which indicate good binding propensity of complexes to DNA and BSA with high binding constant values. Furthermore, the compounds have been investigated for their cytotoxicities on A549 human lung cancer cell. Also the mode of cell death was examined employing various staining techniques and was found to be apoptotic.